HANDLING FOR CHILDREN IN CONFLICT WITH THE LAW BY THE WEST JAVA CHILD PROTECTION AGENCY - Azkiya, Elda Putri; Octaviyana, Tyara; Khoirunnisa, Risma; Kamal, Renata Aulia; Rusmiati, Mia; Achdiani, Yani; Nastia, Gina Indah Permata (Politeknik Kesejahteraan Sosial Bandung, 2025)
This study aims to explore efforts to protect children in conflict with the law in West Java through a qualitative approach. Using a semi-structured interview method, this study collected data from various informants involved in child protection, including Lembaga Perlindungan Anak (LPA) and social workers. The results discussed the stages of practice carried out by the West Java Lembaga Perlindungan Anak (LPA) in handling cases for children in conflict with the law, collaboration between social agencies and stakeholders is essential to create a safe environment for children. This research also identifies patterns and relationships between themes related to child protection, and provides recommendations for improving practices and policies in the field of child protection. Thus, this research is expected to provide practical and theoretical contributions in efforts to strengthen the protection of children in conflict with the law in Indonesia.